Census of the population and housing 1970: Data of demography_4 - Statistics Sweden (Statistics Sweden, 1987)
Data of Demography 1970 consists of three excerpts from the Census of the Population 1970. The first part is a description of the total population by age, marital status and sex with one record/county, administrative district, parish, district, population center. The second describes foreigners and foreign born in administrative districts larger than 50.000 inhabitants and X percent foreigners. One record/person with data on age, sex, marital status, administrative district, population, percent foreigners and citizenship. The third consists of all foreigners. One record/person with information about county, administrative district, population center, sex, marital status, age, country of origin and citizenship. The persons are not identifiable by numbers.

Data of Demography 1970 consists of three excerpts from the Census of the Population 1970. The first part is a description of the total population by age, marital status and sex with one record/county, administrative district, parish, district, population center. The second describes foreigners and foreign born in administrative districts larger than 50.000 inhabitants and X percent foreigners. One record/person with data on age, sex, marital status, administrative district, population, percent foreigners and citizenship. The third consists of all foreigners. One record/person with information about county, administrative district, population center, sex, marital status, age, country of origin and citizenship. The persons are not identifiable by numbers.
Folk- och bostadsräkningen 1970: Demografiska data_4
Keywords: marital status; civilstånd; population distribution; befolkningsfördelning; age distribution; åldersfördelning; Censuses; Folkräkningar; Social Sciences; Samhällsvetenskap